Community Legal Education: Narcotics Prevention and Civil Rights Protection - Seri Mughni Sulubara; Yeni Irma Normawati; Harry Fauzi; Bohari Muslim; Amrizal (Jurnal Pengabdian Masyarakat, 2026)
Purpose: To empower communities through integrated legal education programs that prevent narcotics abuse, safeguard citizens' civil rights, and foster a safer, rights-respecting society. Method: This program employs a community-based, interactive legal education model to prevent narcotics abuse while protecting civil rights. It integrates preventive strategies like early awareness campaigns and rights education, drawing from successful Indonesian initiatives. Practical Applications: Practical applications of "Community Legal Education: Narcotics Prevention and Civil Rights Protection" involve real-world implementations that educate communities on drug risks while upholding rights like fair trials and rehabilitation access. These applications target schools, villages, and youth groups for sustainable impact. Conclusion: Community Legal Education on Narcotics Prevention and Civil Rights Protection effectively bridges knowledge gaps, empowering communities against drug abuse while safeguarding fundamental rights.